Private equity portfolio company fees - Phalippou, Ludovic; Rauch, Christian; Umber, Marc (Journal of Financial Economics, 2018)
In private equity, general partners (GPs) receive fee payments from companies whose boards they control. Fees amount to $20 billion evenly distributed over time, representing over 6% of equity invested by GPs. They do not vary with business cycles, company characteristics, or GP performance. Fees vary significantly across GPs and are persistent within GPs, even after accounting for fee rebates to limited partners (LPs). GPs charging the least raise more capital postfinancial crisis and are backed by more skilled LPs. GPs increase fees prior to going public. We discuss how these results could be explained by optimal contracting and tax arbitrage.